2012
DOI: 10.1152/ajpheart.00783.2011
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and interleukin-1β increase cardiac remodeling during coxsackievirus B3 myocarditis via serpin A 3n

Abstract: Myocarditis and dilated cardiomyopathy (DCM) are often caused by viral infections and occur more frequently in men than in women, but the reasons for the sex difference remain unclear. The aim of this study was to assess whether gene changes in the heart during coxsackievirus B3 (CVB3) myocarditis in male and female BALB/c mice predicted worse DCM in males. Although myocarditis (P = 4.2 × 10(-5)) and cardiac dilation (P = 0.008) were worse in males, there was no difference in viral replication in the heart. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
154
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(174 citation statements)
references
References 46 publications
5
154
3
Order By: Relevance
“…Jiang et al (34) found that overexpression of IL-4 using a plasmid improved survival during acute CVB3 myocarditis, but ϳ75% of WT mice had died by day 8 postinfection. The results from that experiment are not very comparable to this study because in our CVB3 model of myocarditis, nearly 100% of WT mice survive to at least day 90 postinfection (1,13,18,20). Overall, our findings indicate that IL-4 can contribute to cardiac dysfunction in an autoimmune model of CVB3 myocarditis.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Jiang et al (34) found that overexpression of IL-4 using a plasmid improved survival during acute CVB3 myocarditis, but ϳ75% of WT mice had died by day 8 postinfection. The results from that experiment are not very comparable to this study because in our CVB3 model of myocarditis, nearly 100% of WT mice survive to at least day 90 postinfection (1,13,18,20). Overall, our findings indicate that IL-4 can contribute to cardiac dysfunction in an autoimmune model of CVB3 myocarditis.…”
Section: Discussioncontrasting
confidence: 72%
“…Extracellular matrix remodeling and fibrosis are critical for the progression from CVB3 myocarditis to DCM (13,36,43). Fibroblast proliferation and collagen deposition can be increased by TNF, IL-1␤, IL-4, IL-13, IL-17A, and/or TGF-␤ 1 (7,13,18,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found 235 genes that were at least 2-fold regulated in wild-type hearts in response to TAC, and most of these genes showed reduced regulation in both knockout models (Table II in the online-only Data Supplement), whereas 8 genes showed a Ͼ2-fold difference in regulation between cmc-G␣ 13 and cmc-G␣ q/11 -KOs ( Figure IVA in the online-only Data Supplement). Because five of the these genes-tissue inhibitor of metalloproteinase-1 (Timp1), serine (or cysteine) peptidase inhibitor 3N (Serpina3n), tenascin (Tnc), fibromodulin (Fmod), and cartilage oligmeric matrix protein (Comp)-have been implicated in fibrosis, [23][24][25][26][27] we compared the transcriptional regulation of a batch of fibrosis-related genes 14 days after TAC by reverse transcriptase-polymerase chain reaction ( Figure IVB in the online-only Data Supplement). These analyses confirmed that upregulation of Timp1, Serpina3n, and Tnc relied mainly on G␣ 13 , whereas upregulation of Fmod and Comp depended more strongly on G␣ q/11 .…”
Section: Signaling Pathways Mediating the Effects Of G␣mentioning
confidence: 99%
“…Accordingly, we performed a global gene transcriptional analysis on biological replicates of heart tissue from Unc93b1 +/+ mice and Unc93b1 Letr/Letr mice at day 0 and day 2 after infection. Day 2 was examined as TLR activation can occur rapidly in primary human aortic muscle cells following infection [15] and early changes in cardiac signaling can predispose the host to a deleterious outcome as the infection progresses [40]. In addition, significant immune cell infiltration to the heart has not occurred by 48 h after infection, so that gene expression at this time point predominantly reflects the response of resident immune cells and cardiomyocytes.…”
Section: Resultsmentioning
confidence: 99%